Performance Improvement for Port Loading and Unloading Process with Process Mining - Amanda Dewi Paramita; Iwan Vanany (IPTEK Journal of Proceedings Series, 2019)
Port is one of the important things in trade and logistics. The major influence factor of port productivity is the cycle time for loading and unloading. The container activity in port logistics consists of several activities, such as discharging, loading, receiving, delivery, gate-in, and gate-out, among others. These activities using various equipment including container cranes, Rubber Tyred Gantry (RTG), trucks, and other related machinery. The availability of equipment is one of the factors the influence delays in container activities, which can negatively affect productivity. The productivity of the port will affect to Key Performance Indicator (KPI) of the port. The purpose of this study is to analyze the flow of containers that used process mining. Moreover, it provides a recommendation to increase the productivity at Terminal Nilam Multipurpose Port of Tanjung Perak. Process mining method includes many of other analysis, that is discovery, prediction and real-time, bottlenecks and deviation analysis. Disco program used to analyze container activity, besides this, the disco program also use to determine bottleneck mapping that effect to port productivity. The result show delivery and receiving are the cause of the bottleneck. Delivery cancel is known as an activity that inappropriate with the ideal process and indicates as an error in the flow of container activities. The improvement scenario carried out from the results of the analysis obtained is to minimize the occurrence of cancel loading delivery, to obtain a time reduction of ± 11.6 hours. This will affect the productivity of container activities